Alteration to the SWI/SNF complex in human cancers - Vanessa S. Gordon; Colin Rogers; David Reisman (Oncology Reviews, 2011)
The SWI/SNF complex is a key catalyst for gene expression and regulates a variety of pathways, many of which have anticancer roles. Its central roles in cellular growth control, DNA repair, differentiation, cell adhesion and development are often targeted, and inactivated, during cancer development and progression. In this review, we will discuss what is known about how SWI/SNF is inactivated, and describe the potential impact of abrogating this complex. BRG1 and BRM are the catalytic subunits which are essential for SWI/SNF function, and thus, it is not surprising that they are lost in a variety of cancer types. As neither gene is mutated when lost, the mechanism of suppression, as well as the impact of potential gene activity restoration, are reviewed.